Reconditioning and Enhancement of Automatic Pressure Control Equipment for Servo and Regulatory Processes - Suryadi, Aris; Budi Triyono; Hanni Maksum Ardi; Dibyo Setiawan (Universitas Negeri Jakarta, 2025)
Control Systems have taken essential parts widely from industrial world to military equipment. Control systems in the industrial world determine the quality, speed, cost and efficiency of the manufacturing process known as the Process Control System (PCS). The core of the Control System is conditioning (actuators) and reading conditions (sensors). By synergizing those parts with the coordination of the controller, the process value (PV) can be obtained according to the condition of the set point (SP). To get the proper control characteristics, i.e. the fastest possible response, the lowest possible oscillation and offset (error steady state/ESS), an understanding of the concept of a closed loop control system with a continuous scheme is developed. In this regard, the Automatic Control Laboratory under the Pneumatic and Hydraulic Laboratory at the Department of Mechanical Engineering - POLBAN considered to provide students with an introduction to Automatic Instrumentation and Control. The briefing covered the introduction, mechanism and operation of Automatic Instrumentation and Control systems. Therefore, tools were required as a medium for achieving the above competencies, one of which was the modernization of pressure regulators in order to strengthen the Laboratory. Through this research, a rejuvenation and modernization of the control system were carried out by applying a proportional, integral and differential (PID) control system. It was based on a programmable logic controller (PLC) equipped with a human machine interface (HMI) to make it easier to enter set points and PID parameters, to be practical in operation and effective in monitoring and data acquisition. The result of the pressure regulator modernization had the ability to include servo control process (getting a certain value) and regulatory control process (maintaining a certain value) with a continuous closed loop scheme. The modernized pressure control system could be utilized as a prototype demonstration of the system in an actual environment to study and observe the Proportional, Integral and Differential (PID) control system along with the process of determining the parameters Kp, Ti and Td as Practicum equipment.